2011
DOI: 10.3201/eid1708.101328
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 68 among Children with Severe Acute Respiratory Infection, the Philippines

Abstract: TOC summary: Enterovirus 68 was found in 21 children with severe pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 23 publications
6
118
2
5
Order By: Relevance
“…According to our previous reports, most of the EV68 strains detected in the Philippines belonged to lineage 2, and a few of them belonged to lineage 3 (4,10). The VP1 sequences detected in the Philippines and other countries demonstrated that the amino acid sequence patterns in BC and DE loops were correlated with the categorization of EV68 into the 3 lineages (6,8,10).…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous reports, most of the EV68 strains detected in the Philippines belonged to lineage 2, and a few of them belonged to lineage 3 (4,10). The VP1 sequences detected in the Philippines and other countries demonstrated that the amino acid sequence patterns in BC and DE loops were correlated with the categorization of EV68 into the 3 lineages (6,8,10).…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
“…In an enterovirus surveillance conducted in the United States from 1970 to 2005, only a total of 26 strains were reported over 35 years (2). However, the number of reported EV68 cases increased dramatically in the late 2000s, in different parts of the world (3)(4)(5)(6)(7)(8). The underlying molecular mechanism for this sudden increase of EV68 detections in recent years is still unknown.…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
“…It was first detected in 1962 in California, 2 and has since been detected in several countries, including the Philippines, Japan and the Netherlands, as well as in previous clusters in the United States. [3][4][5] However, by the end of 2014, a total of more than 1000 cases from 49 states in the US were reported. 6 Almost 40% of samples submitted to the Centers for Disease Control and Prevention (CDC) for suspected EV-D68 were positive for EV-D68, 6 and the genotype spread further north into Canada.…”
mentioning
confidence: 99%
“…A global upsurge of EV-D68 infections in patients with respiratory tract infections (RTIs) has been observed in recent years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In 2014, a large outbreak of EV-D68 infections occurred in the United States, which raised public health concern owing to severe respiratory illness and neurological complications (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%